2015
DOI: 10.7220/2335-2027.7.4
|View full text |Cite
|
Sign up to set email alerts
|

English for Specific Purposes: Characteristic Features and Curriculum Planning Steps

Abstract: Summary. Knowledge of a foreign language opens new prospects of mobility and collaboration for professionals in the modern world. Education authorities recognize the increased role that foreign languages, especially English, play in the professional development of future specialists and try to introduce this subject at tertiary level. Such courses are aimed at preparing students to effectively communicate in English in their work settings. However, many university students do not have work experience in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…In the group of professional expectations 4% were reported, although the formulation of this expectations were rather vague: to use new knowledge in the future (4%), to become a better teacher (10%). These findings are in line with the study by Belyaeva (2015), stating that "instructors should bear in mind that learners often do not clearly perceive their future professional roles" (p. 87).…”
Section: Resultssupporting
confidence: 90%
“…In the group of professional expectations 4% were reported, although the formulation of this expectations were rather vague: to use new knowledge in the future (4%), to become a better teacher (10%). These findings are in line with the study by Belyaeva (2015), stating that "instructors should bear in mind that learners often do not clearly perceive their future professional roles" (p. 87).…”
Section: Resultssupporting
confidence: 90%
“…Garis besar dari ESP adalah upaya untuk memberikan pembekalan bahasa Inggris kepada para pemelajar (Risan, Mahyuddin, G., 2020) yang sesuai dengan kebutuhannya dalam melanjutkan profesi di komunitas tertentu (Hamidah & Yanuarmawan, 2019) sehingga praktisi ESP perlu untuk membangun goal, tujuan, dan materi pembelajaran sendiri (Belyaeva, 2015). Agar tujuan ESP tercapai, praktisi harus memiliki kemampuan untuk membangun silabus yang sesuai dan memiliki keterampilan pedagogi yang baik.…”
Section: Pendahuluanunclassified
“…The course should start as General English for improving learners' listening comprehension, reading, writing, and speaking skills. Then, the focus can shift towards Discipline Specific English for Academic Purposes to enhance discourse, vocabulary, and register specific to the specialization of study (Belyaeva, 2015). Vanicheva, Kah and Ponidelkoa (2015) concluded that focusing on improving the language of ESP students led to training their memory and enhancing their ability to voice ideas, processes and concepts through applying learnt vocabulary for a specific purpose.…”
Section: Issn 1110-2721mentioning
confidence: 99%